REDUCE TIME PROCESS USING APRIORI ALGORITHM ON K-WAYJOIN BASED TO FIND RETAIL BUSINESS DATA RELATIONSHIP PATTERN - Aryanto, Joko; Asriningtyas, Yuli (University Of Technology Yogyakarta, 2019)
The process of running a trading business, businesses must always update information on market competition that occurs. Running a trading business is not just opening a business place and waiting for consumers to shop. Consumers will lightly come to shopping places to shop for various reasons. From cheap prices, attractive arrangements, large parking lots, to the ease of finding items to buy. From these problems, business people will compete on how to easily attract customers to their place of business.One way to solve these problems is by structuring merchandise with the aim of customers to easily get the items they are looking for. One way to solve these problems is by structuring merchandise with the aim of customers to easily get the items they are looking for. Arrangements that are made do not originate from arranging the location of goods according to taste but are carried out on the basis of trends or trends in goods purchased by consumers when shopping. This process is often referred to as the